1996
DOI: 10.3109/16066359609010751
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in Alcohol Treatment: The Client's Experience of, and Satisfaction with, the Assessment Interview

Abstract: Clients' experiences of routine alcohol assessment interviews at a therapeutic day unit were studied in order to enhance understanding of the factors associated with subsequent engagement in treatment. The paper describes the development and use of the Client's Experiences and Satisfaction Questionnaire. The main finding from its use with 131 clients, was a positive association between the client's perceptions of the quality of the therapeutic relationship established during the interview, and subsequent engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…offered, counselor characteristics, program barriers, program awareness of dropout as a problem, and treatment modality (individual, couples, group) 8, 24 . Positive therapeutic alliance consistently has been related to lower attrition rates 25, 26, 27 . Counselor characteristics such as gender and race have not been related to client attrition, but clinician experience has been related to attrition 28 .…”
mentioning
confidence: 99%
“…offered, counselor characteristics, program barriers, program awareness of dropout as a problem, and treatment modality (individual, couples, group) 8, 24 . Positive therapeutic alliance consistently has been related to lower attrition rates 25, 26, 27 . Counselor characteristics such as gender and race have not been related to client attrition, but clinician experience has been related to attrition 28 .…”
mentioning
confidence: 99%
“… Studies have suggested that differences in the effectiveness of therapists may be related to the therapist's ability to maintain a facilitative stance in the face of client resistance or hostility. The current study, examined a sample of audiotaped sessions from Hyams, Cartwright, and Spratley's (1996) study of engagement in an alcohol treatment service in an attempt to see whether the therapists' effectiveness at engaging clients in treatment was related to client‐therapist interaction in assessment interviews. It was hypothesized that there would be (1) more overall negative interpersonal behaviour (2) more negative interpersonal behaviour by the therapist and (3) more negative interpersonal complementarity in interviews where the client failed to engage.…”
mentioning
confidence: 99%
“…Several of the studies we have already considered in the context of discussing the research concerned with the therapeutic alliance also confirm the importance of these variables for process and outcome in the context of substance use disorders (e.g. Chafetz et al, 1962;Hyams et al, 1996;Miller et al, 1993;Milmoe et al, 1967;VaUe, 1981). These studies suggest the following principle:…”
Section: Other Relational Variables In Psychotherapymentioning
confidence: 65%
“…There also is the Counselor Evaluation of Client Form, on which counselors rate their client on rapport, motivation, and self-confidence (Simpson et al, 1995). Finally, one study used the Client Experiences and Satisfaction Questionnaire, on which clients assess their relationship with a counselor and how well the counselor treated and understood them (Hyams, Cartwright, & Sprately, 1996) .…”
Section: Assessing the Therapist-client Relationshipmentioning
confidence: 99%
See 1 more Smart Citation